Applying the Periprosthetic Joint Infection Consensus Definition to a Case Series of Revision Foot and Ankle Implant-Associated and Infection-Suspected Procedures to Assess Diagnosis. Issue 4 (22nd October 2020) - Baker, Erin A.; Harley, Jackson; Gehrke, Corinn; Ciufo, David J.; Fortin, Paul T.; Vaupel, Zachary M.
Category: Other Introduction/Purpose: Periprosthetic joint infection (PJI) affects 2-3% of all total joint replacement cases. In 10-30% of these cases, the organism is unidentifiable, which may impact treatment planning and outcomes. In this study, suspected periprosthetic infections of foot and ankle procedures treated by four foot and ankle-trained orthopaedic surgeons were retrospectively reviewed to determine culture status and applicability of the 2018 International Consensus Meeting on Orthopaedic Infections (ICM) Revision classification system. Methods: Under an IRB-approved protocol, cases of suspected infection, based on ICD-9/10 codes, from cases performed at a Level 1, private, academic hospital from October 2014 to November 2019 were reviewed for demographic, surgical, and infection-related data. Results: Of the 210 revision cases coded for infection, 82 met the inclusion criteria of the study; cases included removal of an implant and were not wound infection-related only. Preoperatively and intraoperatively, 10 (12%) and 59 (72%) cases were culture-positive, respectively. In this series, 21 (26%) cases met the ICM Revision major criteria and 36 (44%) cases met the threshold for ICM Revision minor criteria; overall, 43 (52%) cases were defined as infected by the 2018 ICM Revision classification system. Conclusion: This study reviewed and identified culture status and infection by the 2018 ICM classification system. In this series of 82 cases, approximately half of the cases met the criteria for infection diagnosis, according to the most recently revised ICM classification system, although nearly three-quarters of the population had at least one positively-identified intraoperative culture. Further data analysis is ongoing to assess the correlation between ICM scoring with pre/postoperative treatment and outcomes.